Landscape features of endangered Ryukyu long-furred rat (Diplothrix legata) roadkill sites in Yambaru, Okinawa-jima Island. Issue 3 (4th May 2021) - Miyamoto, Asako; Tamanaha, Syoko; Watari, Yuya
ABSTRACT: Roadkill poses a significant threat to many wildlife species. To implement habitat management and conservation measures in protected areas, it is important to identify the factors related to roadkill at the landscape scale. The purpose of this study was to clarify the landscape factors involved in roadkill of the endangered Ryukyu long-furred ( Diplothrix legata ) rat in Yambaru, the northern Okinawa-jima Island, Japan. We analyzed the relationship between roadkill sites and landscape factors (evergreen broad-leaved forest area, artificial pine forest area, average vegetation height, and minimum radius of road curve) using a generalized linear model, incorporating spatial autocorrelation using Moran's eigenvector maps along a 13.9 km route using census data from May 2011 to April 2017. In addition, we clarified the relationship between the number of roadkills and national park zoning. Roadkill incidence was found to be positively correlated with average vegetation height and the percentage of pine forest area. The number of roadkill incidents was also higher in zones with higher levels of protection compared to areas with lower or no protection. These results suggest the need for measures in areas containing these landscape elements, such as mature forests and higher percentage of pine forests.